Study on Social Cohesion of The Salafi Group in Banyumas District - Abdul Rohman (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
The title of this article: "Study on Social Cohesion of the Salafi group in Banyumas". The purpose of this study was to determine and find out on social cohesion in the group of Salafi.The methods of this research was used by qualitative approach and its analysis of data using interactive methods. Results from this study: 1) That the Salafist Group came in Banyumas regionÂ Â  approximately the 1980s. Formally, this group has no organization, so they do not have a leader, despite having members of the congregation. If a person be a leader, then the informal nature, and designated are their teachers. 2) Salafi groups are hard to get back to the Qur'an and Sunnah and follow what is done by the as-Salaf as-á¹¢Äliá¸¥ (Ø§Ù„Ø³Ù„Ù Ø§Ù„ØµØ§Ù„ØÂ ) as generation of Companions, Tabi'in and Tabi'it Tabi'in in conducting all activities of life; 3) The social cohesion within the Salafi group is so strong. It is caused by the similarity in following the teachings of which are known to them, recognition of the truths taught by their teachers, and intellectual relationship (study) conducted with its members continuously and do not want to learn except to their teachers.